2015
DOI: 10.1002/adsc.201500681
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Dioxygenation of Alkenes and Terminal Alkynes by using (Diacetoxyiodo)benzene as Oxidant

Abstract: An iron-catalyzed syn-diacetoxylation of alkenes and 1,2-oxyacetoxylation of terminala lkynes has been developed using (diacetoxyiodo)benzenea s oxidant. Ab road range of internal and terminal alkenes, including electron-rich as wella se lectron-deficient alkenes,g avet he desired products in good to excellent yields with high diastereoselectivity (up to > 99:1 dr). In addition the high catalytic activity of iron catalysisfor the 1,2-oxyacetoxylation of terminal alkynes is also reported. Ther oles of catalyst,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 101 publications
1
10
0
Order By: Relevance
“…The articles published by Gade, and Fujita contain some of the examples for dioxygenation of alkenes using TfOH and BF 3 .OEt 2 , respectively. Recently, we have reported an economical method for diacetoxylation of olefins using a homogeneous iron catalyst i.e Fe(OAc) 2 . Recovery of these homogeneous catalysts have somewhat placed limitations on their general use for large or industrial scale operations.…”
Section: Optimization Of the Diacetoxylation Conditions[a]supporting
confidence: 88%
See 1 more Smart Citation
“…The articles published by Gade, and Fujita contain some of the examples for dioxygenation of alkenes using TfOH and BF 3 .OEt 2 , respectively. Recently, we have reported an economical method for diacetoxylation of olefins using a homogeneous iron catalyst i.e Fe(OAc) 2 . Recovery of these homogeneous catalysts have somewhat placed limitations on their general use for large or industrial scale operations.…”
Section: Optimization Of the Diacetoxylation Conditions[a]supporting
confidence: 88%
“…We also found that, the use of 3 equivalents of H 2 O consistently provided high yields of 2 a (Table , entry 8). Based on our previous results, at the end of the reaction Ac 2 O was added to the reaction mixture, which enhances the yield of the desired product to 71 % (Table , entry 9). As it is always advisable to compare the reactivity with other reusable catalysts, the same reaction was conducted using nano CuO, Fe 2 O 3 and Fe 3 O 4 (Table , entries 10–12).…”
Section: Optimization Of the Diacetoxylation Conditions[a]mentioning
confidence: 99%
“…Many elegant methods are developed using hypervalent iodine affording oxyacetoxylation product through C≡C bond activation . Some of the drawbacks of this strategy involves acetic acid at elevated temperature,– and metal catalysts like Fe and Ag . The first report of a metal free oxidation of alkynes was published by Tamura et al .…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mechanism for the formation of enediol diacetates and imidazole derivatives (Scheme 5) is proposed on the basis of the literature. 15,19 First, Ru 3 (CO) 12 is oxidized into Ru 2 (CO) 12 Ru(OAc) 2 , followed by complexation with the alkyne to form intermediate A. Due to steric hindrance, OAc adds to the alkyne from the opposite face to the complexed metal catalyst to give B, Ru 3 (CO) 12 is released from B to produce the target product C. Imidazole derivative G is synthesized from C by aminolysis, accompanied by oxidation of the alcohol into an aldehyde, and further condensation, dehydration, and deprotonation.…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…7). Moreover, Deng and Luo, 17 Biffis and co-workers, 18 Sreedhar and co-workers, 19 and Bäckvall and co-workers. 20 reported that alkynes reacted with PhI(OAc) 2 to afford -acetoxy ketones catalyzed by AgOAc, CuCl(L)(PPh 3 ), Fe(OAc) 2 , Pd(OAc) 2 , respectively (Scheme 1, eqs.…”
mentioning
confidence: 99%